Characteristics of Acute Appendicitis before and during the COVID-19 Pandemic: Single Center Experience - A. Bosak Veršić; M. Šestan; I. Ćepić; H. Nikolić; N. Bukvić; S. Sršen Medančić; D. Hasandić; M. Zelić (Emergency Medicine International)
The aim of the study was to investigate whether the COVID-19 pandemic caused an increased incidence of complicated appendicitis due to the late presentation when compared to the pre-COVID-19 period. Summary Background Data. Acute appendicitis is one of the most common surgical emergencies. During the coronavirus-19 (COVID-19) pandemic, there has been a reported delay in the presentation of some urgencies to the emergency hospital departments. Methods. A total of 427 patients who underwent surgical treatment due to suspected acute appendicitis from June 2019 to November 2020 were retrospectively included in this study. The patients were divided into two groups: the first (pre-COVID-19) group consisted of patients who had surgery before the onset of COVID-19 pandemic (n = 240), while the second (COVID-19) group consisted of those who were operated during the COVID-19 pandemic (n = 187). The primary outcome of the study was to compare the incidence of perforated appendicitis before and during the onset of COVID-19. Results. Overall, 84 patients (19.67%) were diagnosed with perforated appendicitis. We found a weak significance (p=0.085) in the rate of perforated appendicitis between the pre-COVID-19 (17.08%) and the COVID-19 era (22.99%). Conclusions. We did not observe any significant difference in the complications of acute appendicitis before and during the COVID-19 pandemic in a university hospital in Rijeka. An emergent medical care should always be accessible.